Harnessing Recombinant DNA Technology for Modern Innovations: A Review - Kollabathula, Prasuna; Katru, Sreekar; Tumarada, Prasanth; Ravuri, Sakuntala; Akhila, Zainab; Velagala, Sai Keerthi (International Journal of Dental Materials, 2025)
In the past century, controlling gene expressions to enhance desirable traits in living organisms through recombinant DNA (rDNA) technology was merely a concept. However, in recent times, this field has made significant advancements, offering unique benefits to human life. rDNA technology allows for the safe, accessible, and abundant production of crucial proteins for addressing various health issues. Through laboratory methods of genetic manipulation, scientists generate rDNA molecules by merging genetic material from different origins that wouldn’t naturally occur within organisms. Although the chemical structure of DNA is the same across all organisms, the nucleotide sequences vary. The application of rDNA technology extends to diverse fields such as regenerative medicine, nanotechnology, and tissue engineering, allowing for the production of proteins with specific characteristics and effectiveness. This article explores the widespread uses of rDNA technology in basic research, highlighting its crucial role in modern efforts within biological and biomedical sciences, especially in regenerative medicine and nanotechnology fields.